2010
DOI: 10.1074/jbc.m109.073718
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Regulator of G Protein Signaling 19 (RGS19) on Heart Development and Function

Abstract: Wnt/Wg genes play a critical role in the development of various organisms. For example, the Wnt/␤-catenin signal promotes heart formation and cardiomyocyte differentiation in mice. Previous studies have shown that RGS19 (regulator of G protein signaling 19), which has G␣ subunits with GTPase activity, inhibits the Wnt/␤-catenin signal through inactivation of G␣ o . In the present study, the effects of RGS19 on mouse cardiac development were observed. In P19 teratocarcinoma cells with RGS19 overexpression, RGS1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 43 publications
(41 reference statements)
0
16
0
Order By: Relevance
“…This fact suggests that these mice have increased vascular tone from elevated signaling responses to angiotensin. Even though there was hypertension, there was not any cardiac hypertrophy or differences in cardiac systolic contractility that might have contributed to the elevated blood pressure in these mice (Biesemann et al, 2014;Chakir et al, 2011b;Ji et al, 2010;Jones et al, 2012;Momen et al, 2014;Sjogren et al, 2012;Takimoto et al, 2009;Tsang et al, 2010;Yue et al, 2010;Zhang et al, 2006). RGS2 knockout mice had other abnormalities that might contribute to their hypertension.…”
Section: Rgs2mentioning
confidence: 89%
See 4 more Smart Citations
“…This fact suggests that these mice have increased vascular tone from elevated signaling responses to angiotensin. Even though there was hypertension, there was not any cardiac hypertrophy or differences in cardiac systolic contractility that might have contributed to the elevated blood pressure in these mice (Biesemann et al, 2014;Chakir et al, 2011b;Ji et al, 2010;Jones et al, 2012;Momen et al, 2014;Sjogren et al, 2012;Takimoto et al, 2009;Tsang et al, 2010;Yue et al, 2010;Zhang et al, 2006). RGS2 knockout mice had other abnormalities that might contribute to their hypertension.…”
Section: Rgs2mentioning
confidence: 89%
“…In vitro studies showed that overexpressed or reduced RGS19 inhibited cardiomyocyte differentiation by blocking the Wnt signaling pathway through inactivation of the Ga o subunit in mouse F9 embryonic teratocarcinoma cells (Feigin and Malbon, 2007;Ji et al, 2010), which might partially explain the reduced cell proliferation observed in these embryonic hearts. Few littermates of the RGS19 TG mice survived but displayed increased levels of heart failure markers, increased cell proliferation, and abnormal ventricle repolarization, indicating abnormal heart function (Ji et al, 2010).…”
Section: Rgs19/gaipmentioning
confidence: 97%
See 3 more Smart Citations